Pengaruh Teknik Micronizing Jagung Kuning pada Ransum Ayam Isa Brown Leghorn Terhadap Kualitas Isi Telur - Agus Ramadhan; Zakaria Husein Abdurrahman; Purwadi Purwadi (Tropical Animal Science, 2021)
This article presents the results of research on the effect of micronizing techniques on chicken rations isa brown leghorn on the quality of egg contents. Isa Brown eggs are one type of egg that can meet the nutritional needs of people in Indonesia. This study used a completely randomized design (CRD) using 3 treatments. and 6 replications. The analysis used one factor ANOVA test (One Way ANOVA) with SPSS 16.0. Followed by Duncan Multiple Range Test (DMRT) with a level of 5%. Based on the results of the study showed that the yellow corn micronizing technique had a significant effect on egg quality in (1) ration consumption of; (2) Hen day production (HDP); (3) Index albumen; (4) Yolk index; (5) Haugh index, with sig. (P<0.05). While the yellow corn micronizing technique had a significant effect on egg yolk color and eggshell color (P>0.05). The effect of the yellow corn micronizing technique on brown leghorn isa chicken rations on the quality of egg contents showed an increase in quality in the treatment of fine grain yellow corn rations.